A differential diagnosis of melanocytic nevi. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2022)
Silver nitrate is used in dermatology for the therapy of exuberant granulation, especially of the frequent umbilical granuloma; it is also used in hair dyes and more rarely on oral and conjunctival mucous membranes as a disinfectant (3). As well as in medicine it is used in jewelry, analytical chemistry to recognize and measure halogens, photography, etc. In the exogenous pigmentation we have described, the more superficial layers of the stratum corneum are compromised. Contact with sweat chlorine gives rise to silver chloride which under the action of ultraviolet rays forms metallic silver colloids (2); the latter are deposited in the most superficial part of the stratum corneum; due to its sensitivity to light, silver nitrate is stored in dark containers. To prevent dark spots from forming on the skin, it is essential to wear gloves when using silver nitrate. Once the diagnosis of exogenous pigmentation has been made, the patient can be reassured because the continuous regeneration of the epidermis pushes up the superficial silver deposits and ends up eliminating them in about a week. (...).